Amorphous Pterostilbene Delivery Systems Preparation-Innovative Approach to Preparation Optimization - Natalia Rosiak; Ewa Tykarska; Judyta Cielecka-Piontek (MDPI AG, 2023)
The aim of our research was to improve the solubility and antioxidant activity of pterostilbene (PTR) by developing a novel amorphous solid dispersion (ASD) with Soluplus® (SOL). DSC analysis and mathematical models were used to select the three appropriate PTR and SOL weight ratios. The amorphization process was carried out by a low-cost and green approach involving dry milling. An XRPD analysis confirmed the full amorphization of systems in 1:2 and 1:5 weight ratios. One glass transition (Tg) observed in DSC thermograms confirmed the complete miscibility of the systems. The mathematical models indicated strong heteronuclear interactions. SEM micrographs suggest dispersed PTR within the SOL matrix and a lack of PTR crystallinity, and showed that after the amorphization process, PTR-SOL systems had a smaller particle size and larger surface area compared with PTR and SOL. An FT-IR analysis confirmed that hydrogen bonds were responsible for stabilizing the amorphous dispersion. HPLC studies showed no decomposition of PTR after the milling process. PTR's apparent solubility and antioxidant activity after introduction into ASD increased compared to the pure compound. The amorphization process improved the apparent solubility by ~37-fold and ~28-fold for PTR-SOL, 1:2 and 1:5 w/w, respectively. The PTR-SOL 1:2 w/w system was preferred due to it having the best solubility and antioxidant activity (ABTS: IC50 of 56.389 ± 0.151 µg·mL−1 and CUPRAC: IC0.5 of 82.52 ± 0.88 µg·mL−1).